Reviews (Blackfriars, 1934)
La Science du Droit Positif, By Jean Defroidmont. Eusebius Paniphili: A study of the Man and His writings. Five Essays by F. J. Foakes-Jackson. Broadcast Minds. By Fr. Ronald Knox. Skara Brae. A Pictish Village in Orknry. By Professor V. Gordon Childe Smith, B.Litt., etc. With Chaptrrs by Professor T. H. Bryce and Profrssor D. M. S, Watson, F.R.S. Render Unto Caesar. By Margot Robert Adamson. GRAMOPHONE